Hydrodynamic and sediment dynamic impact of human engineering activity on Liyashan oyster reefs, China - Luo, Feng; Chen, Zhipeng; Wu, Hongbo; Zhu, Fei; Zeng, Jingwei; Quan, Weimin (Frontiers in Marine Science, 2022)
Coastal ecosystems are becoming increasingly vulnerable to a range of challenges as human activity increases. Oyster reefs are coastal ecosystems that provide habitat for a diverse range of marine species while also purifying water and providing natural coastal defense. However, as a result of human activity, the global oyster reef area has been drastically diminished and is in grave danger. At the same time, the lack of intuitive and quantitative study methodologies on the impacts of human activities on oyster reefs makes determining the negative impacts impossible. To address this issue, we applied a hydrodynamic model to analyze the impact on oyster reefs. First of all, we considered that human activities, in this paper that is, coastal engineering, mainly affect the development of Liyashan Oyster Reefs by influencing hydrodynamics, sediment concentration, and bed level evolution. Then, we applied MIKE3 to establish a 3D hydrodynamic model of the southern part of the Yellow Sea around oyster reefs and validate it. Finally, the results show that regional variations in flow velocity and suspended sediment concentration would occur in oyster reefs waters, but the magnitude of these variations would be limited. The seabed elevation, however, shows a significant trend of increasing in Center Protection Area, which has a relatively obvious negative impact on oyster reefs. In general, our study can provide a paradigm for analyzing the degree of impact on oyster reefs, showing the advantages of hydrodynamic models in quantitatively analyzing impact factors, and the final results are reliable.